2019
DOI: 10.1590/2177-9465-ean-2018-0320
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneity and aggregation of risk factors for noncommunicable diseases among brazilian adolescents

Abstract: Objective: To estimate the prevalence of concurrency of risk factors for Noncommunicable Diseases and non-random aggregation of these in Brazilian school adolescents. Method: Descriptive study, with data from the National School Health Survey (Pesquisa Nacional de Saúde do Escolar), 2015. The prevalence of concurrent risk factors was estimated: smoking, alcohol use, physical inactivity and low consumption of fruits and vegetables. Aggregation was verified when the observed-expected prevalence ratio was greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…This pattern of clustering was found in a study among Brazilian adolescents. 20 These results suggest that health promotion interventions using multiple health-related behaviours approach should be advocated among adolescents instead of an isolated individual health behaviours approach.…”
Section: Discussionmentioning
confidence: 91%
“…This pattern of clustering was found in a study among Brazilian adolescents. 20 These results suggest that health promotion interventions using multiple health-related behaviours approach should be advocated among adolescents instead of an isolated individual health behaviours approach.…”
Section: Discussionmentioning
confidence: 91%
“…The second most prevalent cluster in Algeria was low fruit and vegetable consumption + low physical activity. Similarly, in Brazil [ 8 ], in the global study [ 5 ], and in Nepal [ 7 ], insufficient physical activity + low consumption of fruits and vegetables was the most prevalent cluster among adolescents. In Brazil, physical inactivity, unhealthy diet, and sedentary behavior was found to be the most prevalent cluster adopted by adolescents (40.1%) [ 18 ].…”
Section: Discussionmentioning
confidence: 98%
“…Clustering of NCDs behavioral risk factors occurs when the observed prevalence of co-occurrence of one or more risk factors exceeds their expected prevalence (O/E ratio >1) in individuals and populations [ 5 ]. Several studies assessed the prevalence of NCDs risk factors and their clustering among adolescents [ 5 , 6 , 7 , 8 ]. One study reported that low fruit and vegetable intake (86.9%) along with physical inactivity (58.6%) were the most prevalent risk factors for cardiovascular diseases (CVDs) among Bangladeshi adolescents [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations